E-KTP SERVICES AT THE POPULATION AND CIVIL REGISTRATION SERVICE OF SOUTH LABUHANBATU REGENCY - Devi Wahyu Ningsy; Teuku Alfiady; Lisa Iryani; Nurhafni; Ahmad Yani (Journal of International Islamic Law, Human Right and Public Policy, 2026)
The Electronic Identity Card (e-KTP) issuance service is one of the population services provided by the Department of Population and Civil Registration to fulfill the public's need for an official identity document. In its implementation, several obstacles still affect the service delivery process. This study aims to analyze the implementation of e-KTP issuance services and identify the factors that hinder their implementation at the Department of Population and Civil Registration of South Labuhanbatu Regency. This study employed a descriptive qualitative research method. Data were collected through observation, interviews, and documentation. The results show that the e-KTP issuance service has been implemented in accordance with the Standard Operating Procedures (SOP). Service officers provide courteous, responsive, and responsible services, supported by adequate facilities and infrastructure. However, the service has not been fully optimal due to several obstacles, including limited public understanding of service procedures, shortages of e-KTP card blanks, network disruptions, and the persistence of brokerage practices. Therefore, greater efforts are needed to improve public outreach, strengthen coordination regarding the provision of e-KTP card blanks, enhance network reliability, and strengthen supervision to prevent brokerage practices in order to improve the implementation of e-KTP issuance services.